PENGARUH PEMBERIAN BOKASI LEGUMENOSE DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL SAWI PADA TANAH ALUVIAL - Sanga Tariu, Are Pabayo; Asnawati, Asnawati; Maulidi, Maulidi (Fakultas Pertanian Universitas Tanjungpura, 2022)
ABSTRACTThis study aimed to obtain the best interaction dose of bokasi legume and NPK fertilizer on the growth and yield of mustard greens on alluvial soil. This research started from 28 April